2021
DOI: 10.22235/cp.v15i2.2069
|View full text |Cite
|
Sign up to set email alerts
|

Structure and invariance of the Hospital Anxiety Depression Scale (HADS) in adolescents

Abstract: The main objective of this study was to test the factorial structure and gender invariance of the Hospital Anxiety Depression Scale (HADS) in a non-clinical sample of 657 adolescents (Mage = 16.3 years; SD = 1.19). The research design was an instrumental investigation, based on a cross-sectional survey with a sample of adolescents in Brazil. The results presented satisfactory evidence of the validity of the factorial structure and gender invariance for the sample. The composite reliability was also satisfactor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
(52 reference statements)
0
3
0
Order By: Relevance
“…Symptoms of anxiety were obtained through the Hospital Anxiety and Depression Scale (HADS) where signs of anxiety were assessed using a previously validated questionnaire for the adolescent population (Cronbach's Alpha coefficients: .84; Bjelland, Dahl, Haug, & Neckelmann, 2002;Faro, Araújo, Maciel, Lima, & Souza, 2021). The HADS classifies the anxiety and depression level and is composed of 14 multiple choice questions where the even questions assess the level of depression and the odd questions assess anxiety.…”
Section: Measurementsmentioning
confidence: 99%
“…Symptoms of anxiety were obtained through the Hospital Anxiety and Depression Scale (HADS) where signs of anxiety were assessed using a previously validated questionnaire for the adolescent population (Cronbach's Alpha coefficients: .84; Bjelland, Dahl, Haug, & Neckelmann, 2002;Faro, Araújo, Maciel, Lima, & Souza, 2021). The HADS classifies the anxiety and depression level and is composed of 14 multiple choice questions where the even questions assess the level of depression and the odd questions assess anxiety.…”
Section: Measurementsmentioning
confidence: 99%
“…It is a screening device for anxiety and depression that, despite its name, has proven to be valid in primary care and useful in psychiatric and psychological work ( 47 , 48 ). Different studies have shown its internal consistency and satisfactory validity for populations of different ages and gender ( 49 , 50 ). Its Portuguese translation by Pais-Ribeiro et al has shown similar properties to the original and confirmed it as reliable and valid ( 47 *).…”
Section: Methodsmentioning
confidence: 99%
“…The cut-off points obtained in the literature were ≥ 9 points for each disorder, proposed from theoretical and empirical criteria derived from clinical samples (Botega et al, 1995;Zigmond & Snaith, 1983). Faro, Fernandes Araújo, Maciel, Lima and Souza (2021) tested the factor structure and gender invariance of the scale in a non-clinical sample of 657 adolescents in Brazil (Mage = 16.3; SD = 1.19) and found satisfactory evidence of factor structure validity and gender invariance for this population. The Composite Reliability was also satisfactory in that study, with an average of the variance explained by the items of 0.31, with a Cronbach's alpha of .84 for the total scale; .81 and .69 for the anxiety and depression subscales, respectively.…”
Section: Instrumentsmentioning
confidence: 99%